HEPATOPROTECTIVE ROLE OF n- HEXANE FRACTION AND CRUDE METHANOLIC EXTRACT OF WITHANIA COAGULANS IN BALB C MICE -A HISTOLOGICAL STUDY - Falak Naz,; Imtiaz, Humaira; Sumaira Javed,; Zainab Rehman,; Shazia Iftikhar,; Waqas Ahmad,; Muhammad Junaid,; Sarosh Asghar, (Journal of Ayub Medical College Abbottabad, 2022)
Background: Withania coagulans is one of the most important medicinal herbs due to its wide range of biological activities. The aim of this study was to compare the hepatoprotective activity of crude methanolic extract versus n- hexane fraction of fruit of Withania coagulans in CCl4 induced liver toxicity Methods: This study was done on 36 Balb c mice in Department of Anatomy of Khyber Medical College Peshawar. Results: The mean serum of Group 1(control Group) was 33.41±1.82U/L, for Group 2 (CCl4 treated Group) was 89.01±7.51 U/L, for Group 3(low dose Group) was 49.91±3.48 U/L and for Group 4 (High dose Group) was 50.86±4.87 U/L. There was significant difference in the readings of Group1 and Group 2 which indicated CCL4 induced hepatotoxicity in two groups. There was significant difference in the values of Group 3 and Group 4 (p-value .000), showing the hepatotoxicity in these Groups was further enhanced. The mean AST at the end of six weeks for Group1 was 26.80±3.21U/L, for Group 2 was 149.01±13.63U/L, for Group 3 (including both low doses) was 70.81±7.92U/L and for Group 4 (High doses group) was 51.01±11.05U/. Conclusion: Withania coagulans both fractions have hepatoprotective effect against CCL4 induced hepatic toxicity in high and low doses in Balb c mice.